DEVELOPMENT OF HOLE RECOGNITION SYSTEM FROM STEP FILE - C. F. Tan; N. Ismail; S.V. Wong; S. Sulaiman; M.R. Osman (Universitas Gadjah Mada, 2005)
This paper describes the development of Hole Recognition System (HRS) for Computer-Aided Process Planning (CAPP) using a neutral data format produced by CAD system. The geometrical data of holes is retrieved from STandard for the Exchange of Product model data (STEP). Rule-based algorithm is used during recognising process. Current implementation of feature recognition is limited to simple hole feat ures. Test results are presented to demonstrate the capabilities of the feature recognition algorithm.